Effects of single session transcranial direct current stimulation on aerobic performance and one arm pull-down explosive force of professional rock climbers - Luo, Jia; Fang, Caihua; Huang, Sen; Wu, Jinlong; Liu, Bowen; Yu, Jingxuan; Xiao, Wen; Ren, Zhanbing (Frontiers in Physiology, 2023)
Objective: To explore the effects of single-session transcranial direct current stimulation (tDCS) on aerobic performance and explosive force in the one-arm pull-down of long-term trained rock climbers. Method: Twenty athletes (12 male and eight female) from the Rock Climbing Team of Hunan province (Huan, China) were selected for a randomized double-blind crossover study. After baseline tests, the twenty subjects visited two laboratories to randomly receive either sham or a-tDCS at a current intensity of 2 mA for 20 min. The two visits were more than 72 h apart. Immediately after each stimulation, subjects completed a 9-min 3-level-load aerobic test and a one-arm pull-down test. Results: Differences in the heart rate immediately after 9-min incremental aerobic exercises revealed no statistical significance between each group (P > 0.05). However, the decrease in heart rate per unit time after exercise after real stimulation was significantly better than before stimulation (P < 0.05), and no statistical significance was observed between after sham stimulation and before stimulation (P > 0.05). One-arm pull-down explosive force on both sides after real stimulation was improved by a-tDCS compared with before stimulation, but with no significant difference (P > 0.05). Real stimulation was significantly improved, compared with sham stimulation on the right side (P < 0.05). Conclusion: Single-session tDCS could potentially benefit sports performance in professional athletes.